Non-Intellective Factors Influencing Academic Performance of Grade 9 and Grade 10 Junior High School Students In Science (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2026)
Non-intellective factors in education are crucial for understanding the holistic nature of learning, as it encompasses emotional, social, and motivational aspects that significantly impact academic performance and engagement. The relationship between these factors and science learning can help educators select optimal teaching methods and interventions to address diverse student needs, leading to a more inclusive and effective learning environment. This study determined the relationship between the non-intellective factors and academic performance in science. The study utilized descriptive-correlational research design to gather data from 110 junior high school students enrolled at Union Christian College for the school year 2021-2022 using the H-Comp scale. The researchers used weighted mean to describe the non-intellective factors, frequency count and percentage for their academic performance in science, and Multiple Regression Analysis to determine the influence of the non-intellective factors in their academic performance. The findings showed that among the non-intellectual factors, intrinsic motivation and study concentration are significant predictors of students' academic achievement in Science, although intrinsic motivation has an inverse relationship with students' academic performance. Meanwhile, all other non-intellectual factors produced insufficient data to be used as predictors of student academic achievement. It further shown a direct relationship between study concentration and student academic success, showing that factors under the students' control have a significant impact on their academic performance. As a result, the researchers encourage students to gain more thoughtful insights into how they can manage their time, self-esteem, and emotions, as well as seek assistance from their family, friends, and teachers. The study concluded that non-intellectual factors in the areas of study, self, and relationships can influence respondents' academic achievement, whereas time management, confidence, anxiety, and support from others are considered to influence students' academic performance.
Keywords: non-intellective factors; science academic performance; learning